Determinant of Hypertension, Obesity and Smoking on Stroke Events in Hospital Patients at Regional General Hospital of Rokan Hulu Riau District, 2018 (Epidemiology and Public Health) - Armaliza Permata Sari; Rahayu Lubis; Zulfendri (Britain International for Academic Research (BIAR) Publisher, 2020)
Stroke is one of the most dominant non-communicable disease complications that can cause death and disability, the number of sufferers continues to increase. The number one cause of death stroke in Indonesia with a proportion of 15.4%. Many factors can cause a stroke, namely factors that can be modified and factors that cannot be modified. This study aims to determine the determinants of hypertension, obesity, smoking of the incidence of stroke in hospitalized patients at the Regional General Hospital of Rokan Hulu Regency, Riau. This type of research is an observational analytic study with a case-control study design with a total sample of 100 people (50 cases and 50 controls) with a ratio of 1: 1. Sampling was done by purposive sampling and using a questionnaire. The independent variables are hypertension, obesity, and smoking. Hypertension using a sphygmomanometer, Obesity using Body Mass Index (BMI) and smoking using a questionnaire. Data analysis was performed by bivariate analysis using simple logistic regression tests and multivariate analysis using multiple logistic regression tests. The results of bivariate analysis with risk factors for stroke events, the most dominant risk factors were hypertension with a value of p = 0.001 and (OR = 5.441, 95% Cl = 2,210-13,397), Obesity with a value of p = 0.026 and (OR = 1,712, 95% Cl = 0,690-4,244), and smoking with p value = 0,037 and (OR = 1,822, 95% Cl = 0,717-4,632). Hypertension is the most dominant risk factor for the incidence of stroke in hospitalized patients in Rokan Hulu District Hospital, while the increased risk of stroke with obesity and smoking is not statistically significant in this study.